ENT 530 Social Media Portfolio: Lily Scarves / Azlin Ramli - Ramli, Azlin (2021)
LILY.SCARVES is a business that is categorize as women clothing which focus on scarves selling. LILY.SCARVES offers a perfect awning scarves to give the satisfaction of customers. It is find that women nowadays always want to look perfect for their appearance. This product offers customers two types of scarves field and various of shades for them to choose. Thus, the price of this product also is affordable and the target market is focus on teenager and adults age 13 – 50 years old. LILY.SCARVES plan to highlight their quality of product and give the best service toward customers followed by the affordable prices offered. This will lead to the better customers’ relationship and may receive more new customer as well as increase in the profit development. Why are we offering for affordable price is because everybody can purchase our product even if they come from lower income group. LILY.SCARVES is managed by myself, Azlin Binti Ramli with my other 2 friends. I have decided to create a Facebook page to promote my business in social media and I found that Facebook page is the best way for me to expand my business to reach more customers. Therefore. I started to learnt on how to make a hard sell post, soft sell post and how to create a teaser for my product. Other than that, I also learn how to make a registration in Go-Ecommerce website to monitor my sales every month. I admitted that it is quite challenging when I do promoting activities through social media because I have to keep updating my page for the customers.